Physicochemical Properties of a Pressurized Deep Eutectic Solvent and Its Application in Extraction Metallurgy - Dianchun Ju; Yunjie Bao; Leyan Jiang; Yingying Li; Chunyu Chen (Metals)
Deep eutectic solvents are widely employed in the recycling and reuse of spent lithium-ion battery cathode materials because of their non-toxicity, low cost, and recyclability. Although DESs have a high recovery rate for metals and are more environmentally friendly, they typically require a longer time or higher temperatures. High temperature and pressure considerably improve leaching efficiency in traditional aqueous systems; this study investigates whether the same is true in DES systems. The physicochemical properties of a DES composed of choline chloride (ChCl) and malonic acid (MA) (1:1) were measured before and after high-temperature and high-pressure treatments, along with their effects on the leaching efficiency of cathode materials for spent lithium-ion batteries (LIBs). The results show that after treatment, the 632.03 cm−1 twisted vibration peak of C-O was red-shifted to 603 cm−1 and the alkyl chain of the DES was lengthened, whereas the 1150.52 cm−1 C-O peak was blue-shifted to 1219 cm−1 and the hydrogen-bonding effect was weakened. At long reaction times, crystals appeared inside the DES. Over time, the crystals increased in size and became less dense, and the color of the material changed from clear to blue to green. After pressurization treatment, the conductivity of the DES increased considerably over its value at atmospheric pressure. The leaching efficiency of Li, Co, Ni, and Mn were 53.20, 47.24, 26.27, and 48.57%, respectively, at 3 h of leaching at atmospheric pressure. The leaching efficiency increased to 78.20, 79.74, 69.76, and 81.80%, respectively, after being pressurized at 3.3 MPa. On this basis, the reaction time was extended to 6 h, and the leaching efficiency of Li, Co, Ni, and Mn were 96.41, 97.62, 98.13, and 97.34%, respectively, trending towards complete leaching. The leaching efficiency of spent LIB cathode materials in DESs was considerably improved under pressurized conditions, providing an efficient method for recovering spent LIB cathode materials using DESs.